2016
DOI: 10.1111/aab.12323
|View full text |Cite
|
Sign up to set email alerts
|

Soil inoculum density of Verticillium dahliae and Verticillium wilt of olive in Lebanon

Abstract: In the Mediterranean basin, Verticillium Wilt of Olive (VWO) is diffused throughout its range of cultivation, causing severe yield losses and tree mortality. The disease was reported in almost all the Mediterranean and Middle East countries, and in Lebanon it is of increasing significance also on many valuable crops. The disease has already been reported on potato, peach and almond in the Bekaa valley; however, to date no information is available about the incidence of VWO and the inoculum density of Verticill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…The selected rivers were surrounded by agricultural fields planted with V. dahliae-susceptible crops, and distributed in the main Lebanese agricultural regions: the Bekaa Valley, North Lebanon, and South Lebanon. In order to define the sampling areas and the number of samples from each river, the locations of infested potato and olive fields, identified in previous studies (Baroudy et al 2016;Habib et al 2017), were plotted on a map in which the main rivers are shown (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The selected rivers were surrounded by agricultural fields planted with V. dahliae-susceptible crops, and distributed in the main Lebanese agricultural regions: the Bekaa Valley, North Lebanon, and South Lebanon. In order to define the sampling areas and the number of samples from each river, the locations of infested potato and olive fields, identified in previous studies (Baroudy et al 2016;Habib et al 2017), were plotted on a map in which the main rivers are shown (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Molecular protocols. For each replicate of the processed dried residues of sediments from rivers and canals and from samples of soil and organic filters residues, two aliquots (0.5 g) were subjected to the extraction of total nucleic acids (TNA) by the cetyltrimethylammonium bromide (CTAB) method (Cullen et al 2001), slightly modified as described by Habib et al (2017). Briefly, extraction was made in 1,000 ml of extraction buffer (0.12 M Na 2 HPO 4 , 1.5 M NaCl, and 2% CTAB) with 50 mg of acid-washed glass beads (425 to 600 mm; Sigma-Aldrich, St. Louis) and two 5-mm steel balls, and the suspension was thoroughly agitated using the mixer mill Retsch MM301 (Retsch GmbH, Haan, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations